Maintenance biofeedback therapy for dysfunctional voiding: Does every child need it?. (28th October 2022) - Dönmez, Muhammet İrfan; Selvi, Ismail; Dereli, Elif; Özgür, Kerime; Oktar, Tayfun; Ziylan, Orhan
Abstract : Objectives: The aim of the present study is to analyze the long‐term clinical outcomes in children who were treated with biofeedback therapy (BF) for dysfunctional voiding (DV) and to determine the need for maintenance of BF due to clinical relapse. Methods: Files of children with DV who underwent BF between 2013 and 2020 were retrospectively reviewed. Patients with neurological or anatomical problems were excluded. A total of 64 patients (52 girls, 12 boys) with a mean age of 8.89 ± 2.48 years who completed the initial BF sessions were included in the study. The demographic and clinical data, dysfunctional voiding symptom scores (DVSS), and uroflowmetry parameters were recorded before and after the initial BF sessions. Clinical success was regarded as the cessation of electromyography activity as well as concurrent resolution of lower urinary tract symptoms and improvement in uroflowmetry parameters. After the initial BF sessions, children who had initial success showed DV relapse at any time during follow‐up received the maintenance BF sessions. Therefore, the patients with successful initial BF were divided into two groups: the group that needed maintenance BF, and the group which required no maintenance BF. Results: Clinical success was achieved in 48 (75.0%) of 64 children following a median of 6 sessions (range 2–8). At the follow‐up, 10 (20.8%) out of 48 patients showed symptom relapse at a median of 8 months (range 2–24 months). After a median of 3.5 maintenance BF sessions (range 1–6), clinical success was observed in all patients. Both groups showed a significant DVSS decrease after initial BF, however, those who needed maintenance had significantly higher DVSS (6.80 ± 2.53 vs. 3.61 ± 1.12, p  < 0.001). At admission, DVSS <17.5 (odds ratio [OR]: 4.31, p  = 0.025) and post‐voiding residual volume as a percentage of estimated bladder capacity for age <28.9 (OR: 5.00, p  = 0.009) were found as the predictive factors for initial BF success. The need for maintenance BF was 2.56‐fold higher with a DVSS above 5.5 after initial BF sessions. Conclusions: Our results show that despite a clinical success rate of 75% after the initial BF, relapse can be seen within 2 years in approximately 20% of the patients. Nevertheless, maintenance of BF may provide clinical success in all patients. Relatively higher DVSS after initial BF can be used as a predictor of the need for maintenance BF.